Aspetti organizzativi e timing - De Biase, P.; Sani, G.; Biancalani, E.; Sangiovanni, M. (Lo Scalpello - Journal, 2019)
TIMING AND SETTINGOpen fractures are often caused by high-energy trauma and the trauma itself is a relevant problem in the approach tothese fractures. Major trauma may lead to significant long-term morbidity and disability. The fracture itself mayinduce prolonged illness lasting up to 2 years after the event. Open fractures are defined as bone fractures associatedwith solution of continuity of the surrounding soft tissue, which puts into communication the external environmentand the bone or haematoma derived from the fracture. This communication with the external environment may leadto higher infection rates, malunion and nonunion if not recognised and treated appropriately. Before 1850, mostsurgeons used to treat open fractures with early limb amputation, since sepsis and gangrene were common side-effects,which often lead to death. It was not until the early twentieth century that sterility techniques became widelyaccepted, in part thanks to the work of English surgeon Joseph Lister. Known as the father of sterile surgery, Lister wasthe first to recognise the importance of sterile techniques during surgery. This way, he managed to reduce mortalityrates dramatically, from 25–50% to 9%. Today, more than a century later, although open fractures are no longer acause of mortality, they are still the source of significant morbidity and disability following trauma.